Synthesis and evaluation of novel metacetamol derivatives with hydrazone moiety as anticancer and antimicrobial agents - ŞENKARDEŞ, SEVİL; MEGA TİBER, PINAR; ORUN, OYA (My University, 2023)
By exploiting the wide biological potential of the hydrazone scaffold, a series of hydrazone derivatives were synthesized, starting from N-(3-hydroxyphenyl)acetamide (metacetamol). The structures of the compounds were determined using IR, 1H and 13C-NMR, and mass spectroscopic methods. The obtained molecules (3 a–j) were evaluated for their anticancer potential against MDA-MB-231 and MCF-7 breast cancer cell lines. According to the CCK-8 assay, all tested compounds showed moderate to potent anticancer activity. Among them, N-(3-(2-(2-(4-nitrobenzylidene)hydrazinyl)-2-oxoethoxy)phenyl)acetamide (3 e) was found to be the most effective derivative with an IC50 value of 9.89 μM against MDA-MB-231 cell lines. This compound was further tested for its potential effects on the apoptotic pathway. Molecular docking studies was also carried out for 3 e in the colchicine binding pocket of tubulin. Additionally, compound 3 e also demonstrated effective antifungal activity, particularly against Candida krusei (MIC=8 μg/ml), indicating that nitro group at the 4th position of the phenyl ring was the most preferable substituent for both cytotoxic and antimicrobial activity. Our preliminary findings suggest that compound 3 e could be exploited as a leading structure for further anticancer and antifungal drug development.
Keywords: Biyomedikal Mühendisliği; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Mühendislik; Mikrobiyoloji; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); ENGINEERING; CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Biyokimya; Genel Kimya; Moleküler Tıp; Moleküler Biyoloji; Bioengineering; Physical Sciences; Biochemistry; General Chemistry; Molecular Medicine; Molecular Biology; Antimicrobial; cancer; hydrazones; metacetamol; molecular docking